FROM HUMAN DISCOURSE TO AUTOMATED DISCOURSE: LINGUISTIC AGENCY AND COMMUNICATION IN THE AGE OF ARTIFICIAL INTELLIGENCE - Rajab Jafarli (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
The rapid integration of artificial intelligence into contemporary communication has introduced a new form of discourse production that challenges traditional assumptions about language, agency, and authorship. Unlike earlier technologies that primarily transmitted human language, AI systems actively generate, interpret, and reshape discourse across academic, professional, and digital environments. This study conceptualizes automated discourse as a hybrid communicative phenomenon emerging at the intersection of human intentionality and algorithmic generation. Drawing on discourse analysis, sociolinguistics, pragmatics, and digital linguistics, the article examines the ontological distinction between human and AI-generated discourse, the structural mechanisms of AI language production, and the transformation of authorship in human–AI interaction. In addition to its theoretical framework, the study incorporates an empirical component based on survey data collected from academics across universities in Azerbaijan, including a significant proportion of linguists. The findings reveal that AI-generated discourse is perceived as neither fully equivalent to nor entirely distinct from human discourse, reflecting an emerging epistemological ambiguity. The results further demonstrate a shift toward distributed authorship, increasing recognition of AI as a communicative participant, and a substantial influence of AI on linguistic practices and stylistic norms. The study also highlights cautious but growing trust in AI-generated content, alongside strong consensus regarding the need for ethical transparency in AI-assisted communication. Participants widely anticipate a future characterized by hybrid communicative ecologies in which human and AI contributions are increasingly intertwined. The article argues that artificial intelligence should not be understood as replacing human communication, but as reconfiguring the ecology of discourse by expanding the modes through which language is produced, circulated, and interpreted. It concludes that automated discourse represents a structurally grounded, empirically observable, and transformative development in the evolution of language, requiring linguistics to move beyond exclusively human-centered models and to incorporate non-human yet socially meaningful language production into its theoretical scope.